2011
DOI: 10.1186/1471-2334-11-177
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of treatment with pegylated interferon and ribavirin in an unselected population of patients with chronic hepatitis C: A Danish nationwide cohort study

Abstract: BackgroundThe effect of peginterferon and ribavirin treatment on chronic hepatitis C virus (HCV) infection has been established in several controlled clinical studies. However, the effectiveness of treatment and predictors of treatment success in routine clinical practice remains to be established. Our aim was to estimate the effectiveness of peginterferon and ribavirin treatment in unselected HCV patients handled in routine clinical practice. The endpoint was sustained virological response (SVR), determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
2
13
0
2
Order By: Relevance
“…[11][12][13][14][15] In contrast, most of the studies from USA, Europe and Japan have reported a prevalence rate of 60%-70% of genotype 1b and 1a in patients with CH-C. 16 HCV treatment responses vary with the genotype, with the highest SVR rates observed for genotype 2, 3 (72-80%) and the lowest rates observed for genotypes 1 and 4 (44-50%). 13,[17][18][19] Our study population also showed similar results as genotype 1 (20%) had significantly low SVR as compared to genotype 3/2 (92.0%).…”
Section: Discussionsupporting
confidence: 63%
“…[11][12][13][14][15] In contrast, most of the studies from USA, Europe and Japan have reported a prevalence rate of 60%-70% of genotype 1b and 1a in patients with CH-C. 16 HCV treatment responses vary with the genotype, with the highest SVR rates observed for genotype 2, 3 (72-80%) and the lowest rates observed for genotypes 1 and 4 (44-50%). 13,[17][18][19] Our study population also showed similar results as genotype 1 (20%) had significantly low SVR as compared to genotype 3/2 (92.0%).…”
Section: Discussionsupporting
confidence: 63%
“…Some investigators found female gender as the positive predictor for SVR in RCT and in "real life condition"studies [9,24,25,56,63,64]. The others did not confirm these results [20,40,42,44,65], or even found that response to combined treatment and SVR in females 50 years old or older was poorer than in males [66]. Low estrogens level in older women could be responsible for their impaired response to antiviral treatment.…”
Section: Discussionmentioning
confidence: 65%
“…Patients infected with "easy-to-treat" genotypes 2 and 3 respond much better than those with "difficult-to-treat" genotypes 1 and 4. HCV genotype, pretreatment viral load, ethnicity, gender, presence of cirrhosis or advanced fibrosis, obesity, steatosis, insulin resistance, elevated γGT and other are significantly associated with the outcome of Peg-IFN plus RBV combination therapy [32,[34][35][36][37][38]. Furthermore, those with low pretreatment viral load respond much better than those with high pretreatment viral load.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Genotype 7 ble nylig påvist i Afrika og er ikke testet for i den aktuelle perioden (1). Vi har begrensede data fra Skandinavia om effekten av hepatitt C-virusbehandling administrert i vanlig klinisk praksis (9,10).…”
unclassified